Legal Action of Wisconsin Report on Milwaukee's Housing Crisis, Foreclosure, Evictions, and Subprime Lending - (:unkn) unknown (My University, 2007)
his report was prepared by the Employment and Training Institute for Legal Action of Wisconsin to identify low-income populations in Milwaukee County with legal needs related to evictions, foreclosures, and mortgage lending practices. The number of foreclosure cases filed with the Milwaukee County circuit courts has risen to all-time highs, directly tied to increased mortgage lending activity for low-income households. Foreclosure cases reaching the Milwaukee County Sheriff’s Office for auction sales have also shown dramatic increases and in the last five years averaged 143 per month, peaking at an all-time high of 229 in January 2007. Eviction cases filed with the Milwaukee County small claims court have increased to an all-time high during the past year. While many evictions are for failure to pay rent, foreclosure-related evictions make up an increasing share of eviction cases and are well above the levels reported in prior years.
Keywords: foreclosures; predatory lending; subprime lending; morgages; evictions